If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-5p-9=2(p-2)-6p
We move all terms to the left:
-5p-9-(2(p-2)-6p)=0
We calculate terms in parentheses: -(2(p-2)-6p), so:We get rid of parentheses
2(p-2)-6p
We add all the numbers together, and all the variables
-6p+2(p-2)
We multiply parentheses
-6p+2p-4
We add all the numbers together, and all the variables
-4p-4
Back to the equation:
-(-4p-4)
-5p+4p+4-9=0
We add all the numbers together, and all the variables
-1p-5=0
We move all terms containing p to the left, all other terms to the right
-p=5
p=5/-1
p=-5
| 3x-15-6x=12 | | 25+8x=9x+21 | | B+3(b+3)=5 | | -1=t-10 | | 5-(5-8n)=8n | | 9+7a-a=-3 | | -6=s-10 | | *6(5x+2)=198 | | x=-4*3-12 | | v-15=-4 | | 8x+16=-8(x+8) | | j+12=-6 | | x=-4(3)-12 | | -3z/4=18 | | Y=4(x+8)(x-6) | | b-6=5b-3b-14 | | x/3=-33 | | 4(x+2)=5(2x+3) | | 15=f+3 | | (4x+8)+(2x+2)+26.25=180 | | 3(x-2)=2x+6(x-1) | | 2=3n-1+1 | | 5x=7x/12 | | 3x=-3(x+2) | | j-5=2 | | 16=2x-x/4 | | 21x-9+53=180 | | 15m-22=-10m+28 | | Q=25-0.2p | | 3x+5=25+13x | | 17x+26=6x+x+56 | | x+23/28=2 |